Numerical simulations for fractional variation of (1+1)-dimensional Biswas-Milovic equation - Korpinar, Zeliha; İnç, Mustafa (Elsevier Gmbh, Urban & Fischer Verlag, 2018)
In this work, the residual power series method (RPSM) is used to solve fractional variation of (1 +1)-dimensional Biswas-Milovic equation that defines the long-space optical communications. The RPSM gets Maclaurin expansion of the solution. The solutions of present equation are computed in the shape of quickly convergent series with quickly calculable fundamentals by using mathematica software package. Explanation of the method is given graphical consequens and series solutions are made use of to represent our solution. The found consequens show that technique is a power ansd efficient method in conviction of solution for the fractional (1 + 1)-dimensional Biswas-Milovic equation. (C) 2018 Elsevier GmbH. All rights reserved.
Keywords: Residual power series method; (1+1)-Dimensional Biswas-Milovic equation; Series solution